The Influence of Corporate Image and Service Quality on Consumer Decisions to Use Delivery Services at J&T Express Bintaro Branch - Ahmad Nurhadi; Umi Nariawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine the effect of corporate image and service quality on consumer decisions to use delivery services at J&T Express Bintaro Branch. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that corporate image has a significant effect on purchasing decisions by 40.8%, hypothesis testing is obtained t count > t table or (8,183 > 1,985). Service quality has a significant effect on purchasing decisions by 41.7%, hypothesis testing is obtained t count > t table or (8,331 > 1,985). Corporate Image and Service Quality simultaneously have a significant effect on Purchase Decisions with the regression equation Y = 9,720 + 0.380X1 + 0.375X2 and the contribution of the influence is 51.8%, hypothesis testing is obtained F count > F table or (51,601 > 2,700.